Territoriality among Northeastern Algonquians - Bishop, Charles A. (Anthropologica, 2022)
Since Frank Speck first described the Northeastern Algonquian family hunting (trapping) system, scholars have attempted to account for its origin and spatio-temporal existence. Because historical studies challenged the aboriginality of this system, enticing evidence suggesting precontact territoriality has been ignored and/or explained away in terms of historic fur trade factors. Inasmuch as they influence land use patterns, data from the St. Lawrence-Upper Great Lakes area and the boreal forests of Quebec and Ontario are examined in terms of sociopolitical and economic developments. Since some early seventeenth century groups in the Upper Great Lakes region appear to have been socially ranked, it is shown that socially important positions were closely related to a regional transactional alliance system that included the maintenance of social boundaries. It is also suggested that socially important positions were closely related to the territorial control of exchange resources. Whether prehistoric boreal forest peoples who were part of the alliance system were also territorial is uncertain, although postcontact developments help to explain very early examples of this.